(untitled) (Global Journal of Science Frontier Research, 2016)
A cross sectional study was carried out at Wolaita Sodo district from May 2013 to November 2014 with the aim to evaluate the bacteriological quality and to isolate and identify common milk borne zoonotic bacterial pathogens (Staphylococcus aureus, Escherichia coli, and Salmonella species) from raw cow milk and cheese collected in market, restaurant and cafeteria. Milk quality related practice was also assessed by direct observation and questionnaire survey. A total of 56 raw milk and 40 cheese samples were collected in cafeterias / restaurants and from market. The result revealed that 43(76.7%) were poor quality milk with a total aerobic bacterial count more than 5×10 5 CFU/ml and only 13(23.3%) moderate or acceptable milk which have an estimated total aerobic bacterial count of below 5×10 5 CFU/ml. The mean total bacterial count and mean of coliforms count was significantly higher (P